Exploitation of Child Rights in Islamic Family Law Perspective - Sri Asmita; Muhammad Abdillah; Ifrohati; Lusiana; Hana Pertiwi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Exploitation of children has changed the perspective and morality of humans towards criminal law, at the same time government policies have made a clear regulation on the enforcement of legal protection for children who are victims of exploitation. The study is based on the argument that there is no law enforcement on the practice of child exploitation so that exploitation continues to occur continuously. This study applies a literature study approach and policy review and various data sourced both online and offline which will later be able to provide an objective picture of how child exploitation is in law from the perspective of Islamic family law. As has been found in previous research on punishment for perpetrators of child exploitation, it has ignored the justice of children victims of exploitation by their parents, close people and community agencies. Law enforcement cannot guarantee absolute rights for children autonomously, this is due to many considerations so that legal protection for child victims of exploitation is very difficult to enforce. Thus, a discussion is needed to provide legal protection for child victims of exploitation with the perspective of Islamic family law.